2001
DOI: 10.1289/ehp.01109539
|View full text |Cite
|
Sign up to set email alerts
|

Possible estuary-associated syndrome: symptoms, vision, and treatment.

Abstract: The human illness designated as possible estuarine-associated syndrome (PEAS) by the Centers for Disease Control and Prevention (CDC) has been associated with exposure to estuaries inhabited by toxin-forming dinoflagellates, including members of the fish-killing toxic Pfiesteria complex (TPC), Pfiesteria piscicida and Pfiesteria shumwayae. Humans may be exposed through direct contact with estuarine water or by inhalation of aerosolized or volatilized toxin(s). The five cases reported here demonstrate the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
34
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…The VCS deficits spanned the spatial frequency spectrum in both exposed groups, similar to the VCS deficit profiles seen in other solvent exposed populations (21)(22)(23)(24)(25)(26) and in contrast to the VCS spatial-frequency profiles observed in populations exposed to methyl mercury (44,45) and inorganic mercury (46,47). Differences between the shapes of altered VCS spatial-frequency profiles can indicate differential effects of various toxic exposures (40)(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The VCS deficits spanned the spatial frequency spectrum in both exposed groups, similar to the VCS deficit profiles seen in other solvent exposed populations (21)(22)(23)(24)(25)(26) and in contrast to the VCS spatial-frequency profiles observed in populations exposed to methyl mercury (44,45) and inorganic mercury (46,47). Differences between the shapes of altered VCS spatial-frequency profiles can indicate differential effects of various toxic exposures (40)(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Discussionsupporting
confidence: 59%
“…High levels of airborne perc in occupational exposure studies (280,060-83,080 µg/m 3 ) have been associated with increased neurologic symptoms (19) and deficits on cognitive and motorspeed tasks (16)(17)(18) that depend heavily on visual system function (48). Deficits in color discrimination have been reported at lowerlevel (41,245 µg/m 3 ) occupational exposures (14,15). Altmann and colleagues (20) reported deficits in visual memory, simple visual reaction times and complex visual reaction times in residents near dry-cleaning facilities where mean indoor air perc concentration was 4,980 µg/m 3 (median = 1,360 µg/m 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VCS deficit greatest at midspatial frequencies (i.e., midsize dark and light bar sinusoidal gratings) was similar to but larger than that observed in the North Carolina estuarine cohort (13,17). Treatment with the toxin-binding polymer cholestyramine (CSM) (20) to increase toxin(s) elimination rate led to symptom abatement and VCS recovery in all cases within 2 weeks of treatment initiation (19). Cases with repeated acquisition of PEAS showed VCS loss, followed by recovery with CSM treatment on each occasion (19).…”
mentioning
confidence: 58%
“…A report on nonoccupationally related, acute, and chronic PEAS cases diagnosed at a private medical clinic in Pocomoke City, Maryland, indicated that a VCS deficit was present in subjects with either conditions (19). The VCS deficit greatest at midspatial frequencies (i.e., midsize dark and light bar sinusoidal gratings) was similar to but larger than that observed in the North Carolina estuarine cohort (13,17).…”
mentioning
confidence: 80%